Why the FBI Can't Build a Case Management System. - Israel, Jerome (Computer (00189162), 2012)
A review of the problems that haunted the FBI's Virtual Case File and Sentinel case management programs and an examination of the technical reasons for these failures provide the basis for recommendations to help avoid their repetition.